Layanan Konseling Kelompok dengan Teknik Modeling Untuk Mengatasi Perilaku Bullying Pada Anak di Panti Asuhan Al Yamin - Rada Yulia; Zhila Jannati; Emi Puspita Dewi (Social Science and Contemporary Issues Journal, 2024)
This study is entitled "Group Counseling Services with Modeling Techniques to Overcome Bullying Behavior in Children at Al-Yamin Orphanage". Bullying is aggressive behavior that is done repeatedly with the aim of hurting or intimidating others, which has a negative impact on both the victim and the perpetrator. Efforts to overcome bullying behavior can be done through group counseling services with modeling techniques. This study aims to determine the description of bullying behavior in orphanage children, the application of group counseling services with modeling techniques to overcome bullying behavior, and to determine changes in bullying behavior after the application of group counseling services with modeling techniques. The research method used is a qualitative approach with a descriptive type. Data collection is carried out through interviews, observations, and documentation, with data analysis including data reduction, data presentation, and conclusions. The subjects of this study were five children involved in bullying behavior who showed aggressive behavior and difficulty in building empathy. Through group counseling services with modeling techniques, children experienced positive changes, namely a decrease in bullying behavior, an increase in empathy, and improvements in social interaction. Modeling techniques have been proven effective in addressing bullying behavior by providing concrete examples of expected behavior and giving children the opportunity to practice it.